2010
DOI: 10.1038/jcbfm.2010.33
|View full text |Cite
|
Sign up to set email alerts
|

Human Recombinant Tissue-Plasminogen Activator (Alteplase): Why Not Use the ‘Human’ Dose for Stroke Studies in Rats?

Abstract: Since a pioneer work that has shown in vitro that the rat's fibrinolytic system is 10-fold less sensitive to recombinant tissue-plasminogen activator (rtPA) than the human system, most preclinical studies are performed with 10 instead of 0.9 mg/kg rtPA (the clinical dose in stroke patients). In this study, we compared the effects of these doses on mean time to reperfusion, reperfusion slope, brain infarct volume and edema in a rat model of thrombo-embolic stroke. Our data provide evidence that the dose of 0.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 15 publications
4
37
0
Order By: Relevance
“…In the second experiment, 20 rats were randomly divided into four equal groups as noted above, and these animals were used for the evaluation of BBB permeability and levels of MMP-9. The dose of r-tPA and AA was selected based on the other investigations [14,18] and our preliminary results. The drugs were applied at 5 hr after the stroke onset.…”
Section: Methodsmentioning
confidence: 99%
“…In the second experiment, 20 rats were randomly divided into four equal groups as noted above, and these animals were used for the evaluation of BBB permeability and levels of MMP-9. The dose of r-tPA and AA was selected based on the other investigations [14,18] and our preliminary results. The drugs were applied at 5 hr after the stroke onset.…”
Section: Methodsmentioning
confidence: 99%
“…A single clot measuring 40 mm in length was injected in a volume of 50 l saline solution through a polyethylene-10 catheter directed into the internal carotid artery up to 2 mm after the pterygopalatine-internal carotid artery bifurcation, as detailed previously. 29 After a 45-min period of occlusion during which all rats were given medical air, the catheter was removed from the internal carotid artery to the external carotid artery, and the rats were given tPA in the form of Actilyse at 0.9 mg/kg (a dose shown to be as clinically relevant as that of 10 mg/kg, which is often used in rodents 31 ) in 1 ml saline solution (10% bolus plus 90% perfusion over a 45-min period) with either medical air (n ϭ 5) or 75 vol% nitrous oxide (n ϭ 5). Then, all animals were given medical air again.…”
Section: Mcao Experiments With Intraischemic Nitrous Oxidementioning
confidence: 99%
“…Haelewyn et al showed that the dose of 0.9 mg/kg rtPA (the clinical dose in patients with stroke) is as appropriate as that of 10 mg/kg for preclinical stroke studies in rodents. 22 Aronowski et al found that 10-mg/kg dose of intravenous rtPA started 5 minutes after 180 minutes of MCAO was very toxic and resulted in severe bleeding and high mortality in animals and suggested that 5 mg/kg rtPA produced bleeding in approximately 85% to 90% of animals. 9 Accordingly, we used a total dose of 5 mg/kg (2.5 mg/kg bolus followed by 30-minute intravenous infusion at 5 mg/kg per hour) and rtPA was started 15 minutes after the onset of reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Statistically significant effects were detected among all 3 groups when compared with the control: for forelimb foot fault placing ( Figure 3B; F [2,22] ϭ6.08, PϽ0.01), parallel bar traversing ( Figure 3C; F [2,22] ϭ14.75, PϽ0.01), and beam balance ( Figure 3D; F [2,22] ϭ22.70, PϽ0.01). The post hoc test indicated that significant improvements in motor behavior were achieved by each treatment in ischemic rats from 2 through 28 days after stroke.…”
Section: Ethanol In Combination With Hypothermiamentioning
confidence: 96%